Thesaurus on gender and sexual and reproductive health and rights - Manglal-lan, Christine M. (2006)
The gender and sexual and reproductive health and rights (G&SRHR) thesaurus was developed to function both as a cataloging and searching tool. The hybrid system of natural and controlled vocabularies for term analysis and classification was applied as research design. Inductive method was utilized.